Social and environmental conditions related to Mycobacterium leprae infection in children and adolescents from three leprosy endemic regions of Colombia - Serrano-Coll, Héctor (BMC Infect Dis, 2019)
BACKGROUND: Leprosy is is still considered a public health issue and in Colombia 7–10% of new cases are found in children, indicating both active transmission and social inequality. We hypothesized that circulating antibodies against Natural Octyl Disaccharide-Leprosy IDRI Diagnostic (NDO-LID) (a combination of Mycobacterium leprae antigens) could reveal the social and environmental aspects associated with higher frequencies of M. leprae infection among children and adolescents in Colombia. METHODS: An observational cross-sectional study was conducted involving sampling from 82 children and adolescents (younger than 18 years of age) who had household contact with index leprosy patients diagnosed in the last 5 years. Data were analyzed through bivariate analysis made by applying a Pearson x(2) test for qualitative variables, while quantitative variables, depending on their distribution, were analyzed using either a Student’s t-test or Mann-Whitney U test. Multivariate analysis was performed using a multiple regression and binomial logistic approach. RESULTS: A bivariate analysis demonstrated that antibody titers against NDO-LID were significantly greater in children and adolescents with a low socioeconomic status that had: lived in vulnerable areas of the UAChR shared region; eaten armadillo meat; exposure of over 10 years to an index case and; not received BCG immunization. Moreover, a multivariate analysis showed that residing in the UAChR region has a strong association with a greater possibility of M. leprae infection. CONCLUSIONS: M. leprae transmission persists among young Colombians, and this is associated with social and environmental conditions. An intensification of efforts to identify new leprosy cases in vulnerable and forgotten populations where M. leprae transmission continues therefore appears necessary. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-019-4120-2) contains supplementary material, which is available to authorized users.